Modeling for appropriate awareness of H1N1 influenza among urban population of Vadodara, India - Suresh Kumar Rathi; Hardik Gandhi; B. S. Bhavsar (Indian Association of Preventive and Social Medicine, 2011)
H1N1 influenza is a viral disease. World Health Organization declared it phase 6 level of pandemic. India, especially Gujarat suffered most from its high case fatality rate. Hence, it was decided to assess awareness level through modelling about H1N1 influenza in urban population of 18 years and above of Vadodara, India.